2012
DOI: 10.1177/1473871612465214
|View full text |Cite
|
Sign up to set email alerts
|

Designing a better weather display

Abstract: Weather maps commonly display several variables at once, usually a subset of the following: atmospheric pressure, surface wind speed and direction, surface temperature, cloud cover, and precipitation. Most often, a single variable is mapped separately and occasionally two are shown together. But sometimes there is an attempt to show three or four variables with a result that is difficult to interpret because of visual interference between the graphical elements. As a design exercise, we set the goal of finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Iconic displays is another visualization technique that maps various attributes of multidimensional data to features such as color, shape of an icon, or glyph. Glyphs are commonly used in weather and ocean data displays for showing wind speed and direction [WP13], and for displaying ocean currents [RSAS17]. Pilar and Ware [PW13] evaluated various glyphs and streamlines and showed that integrating glyphs along with streamlines is useful in understanding patterns in flow visualization.…”
Section: Taxonomiesmentioning
confidence: 99%
“…Iconic displays is another visualization technique that maps various attributes of multidimensional data to features such as color, shape of an icon, or glyph. Glyphs are commonly used in weather and ocean data displays for showing wind speed and direction [WP13], and for displaying ocean currents [RSAS17]. Pilar and Ware [PW13] evaluated various glyphs and streamlines and showed that integrating glyphs along with streamlines is useful in understanding patterns in flow visualization.…”
Section: Taxonomiesmentioning
confidence: 99%
“…Despite the visualization community's promotion of more perceptually appropriate alternatives [BGP∗11, BRT95, Mor09, Tru81, LH92, Gre08, KRC02], rainbow color maps remain commonplace in a variety of scientific domains, including medicine [BGP∗11], atmospheric and climate sciences [QM16, DPW∗15], bioengineering [BTGM16], aerospace [KES13], and astronomy [ZDM∗15]. Although domain convention is often used to justify the inclusion of rainbow color map variants in visualization systems [WP13, QM16, PWB∗09], we still do not understand why experts continue to gravitate to spectral schemes. Cited reasons include familiarity [BGP∗11, QM16], aesthetic preference [BGP∗11, Bre97, Mor16], and ease of use [BT07, Mor16], but evidence also suggest that rainbow color maps may be a satisficing design choice for specific types of tasks, such as locating and quantifying extreme values [DPW∗15, WTS∗17, WTB∗18, RNA18, War88, WTB∗18].…”
Section: Discussionmentioning
confidence: 99%
“…Using motion to encode variables is common in vector field visualization. Recently, Ware and Plumlee showed that encoding wind direction (Figure 3(l)) using animated traces results in a lower percetual error rate than three static methods [WP13].…”
Section: Evidence Supporting Visual Multiplexingmentioning
confidence: 99%